The two-site Heisenberg model studied using a quantum computer: A didactic introduction - Oliveira, M.G.J.; Antão, T.V.C.; Peres, N.M.R. (Revista Brasileira de Ensino de Física, 2024)
The two-site Heisenberg model has an extraordinarily simple analytical solution and is traditionally used as a benchmark against numerical methods, such as exact diagonalization and Monte Carlo methods. In the same spirit, we benchmark three quantum algorithms that are implemented in a quantum computer against the analytical solution of this model. In particular, this presentation includes a description of the standard and iterative quantum phase estimation algorithms, as well as the variational quantum eigensolver. These quantum algorithms are introduced in a pedagogical fashion allowing newcomers to the subject, familiar with only the most basic quantum mechanical systems, to easily reproduce the presented results and apply the methods to other problems, thus building a seemingly under-appreciated path towards useful quantum algorithms through the lens of simulating and computing properties of physical quantum systems. O modelo de Heisenberg de dois sítios tem uma solução analítica extraordinariamente simples e é tradicionalmente usado como um ponto de referência para métodos numéricos, como a diagonalização exata e métodos de Monte Carlo. Nessa linha de pensamento, comparamos três algoritmos quânticos implementados num computador quântico com a solução analítica deste modelo. Em particular, este trabalho inclui uma descrição dos algoritmos quânticos tradicional e iterativo para a estimação de fase, bem como o variational quantum eigensolver. Estes algoritmos quânticos são introduzidos de forma pedagógica, permitindo que leitores familiarizados apenas com os sistemas quânticos mais básicos, reproduzam facilmente os resultados apresentados e apliquem os métodos a outros problemas, construindo assim um caminho, aparentemente subestimado, para algoritmos quânticos úteis através da simulação e cálculo de propriedades de sistemas quânticos.